Electrochemical Sex Determination of Dioecious Plants Using Polydopamine-Functionalized Graphene Sheets - Fu, Li; Wang, Qiao; Zhang, Mingjun; Zheng, Yuhong; Wu, Mengyao; Lan, Ziyi; Pu, Jiansong; Zhang, Huaiwei; Chen, Fei; Su, Weitao; Yu, Jinhong; Lin, Cheng-Te (Frontiers in Chemistry, 2020)
The rapid identification of sex has potential uses involving dioecious commercial plants. In this work, we first propose a rapid electrochemical analysis method for plant sex determination using the signal difference generated by the electrochemically active substances in plant tissue. Polydopamine-functionalized graphene was wrapped around plant tissue. The introduction of polydopamine-functionalized graphene could solve the problem of the instability of plant tissue immobilization and enhance the electrochemical signals from plant tissue. Taxus × media, Dioscorea zingiberensis and Dioscorea bulbifera were deliberately selected as dioecious plant models due to their pharmaceutical applications. The sex of the plant was not obvious after simply comparing the electrochemical voltammograms. Scatter patterns and 3D surface patterns were generated based on the voltammograms recorded after different solvent extractions. Sex determination was successfully achieved by pattern recognition.